Strategi Budaya dalam Filsafat Erich Fromm - Kumari, Fatrawati (Khazanah: Jurnal Studi Islam dan Humaniora, 2015)
Abstract: The aim of this study is to determine the formulation of Frommscultural strategy and find its relevance to national cultural strategy. This qualita-tive -philosophical study is presented through the synthesis analysis of the psy-choanalyst Freud and socio-economist Marx. The conclusion is that the for-mulation of Fromms culture strategy rooted in the concept of to be. To be isa way of being existential human, characterized by being active, that is theoptimal use of the human strengths for productivity, which tends to makechanges and is interested in goodness, also tends to give and love. The culturalstrategy is then formulated from the concept of to be. This is an attempt tocreate a new culture which includes material and non-material aspects. Materialaspects include social, economic and political structure, while the non-materialaspects includes individual-social character, ideas and objectives of the com-munity in the form of norms, values, dogma, ideology and so forth. Theseaspects are interacting and influencing each other. The orientation of to be willaffect the economic structure, and then form a social character and subse-quently form an idea. Furthermore, the cycle runs in reverse in the relationaldynamic series.